How Does Supervisory Family Support Influence Employees' Attitudes and Behaviors? A Social Exchange Perspective. (May 2014) - Bagger, Jessica; Li, Andrew
In this two-study article, the authors investigate the mechanism through which supervisory family support is linked to outcome variables and examine the moderating effect of family-friendly benefits on this relationship. Drawing on social exchange theory, they propose and find that the quality of leader–member exchange, a form of social exchange relationships, mediated the relationship between supervisory family support and work-related outcomes in Study 1 ( N = 82). Furthermore, in Study 2 ( N = 225), the model linking supervisory family support to outcome variables through social exchange relationships was moderated by the level of family-friendly benefits offered by the organization. Implications for research and practice are discussed.